Fluoride inhibition of wine yeasts : a thesis presented in partial fulfilment of the requirements for the degress of Master of Science in Microbiology at Massey University - Clayton, Miranda Gaye (Massey University, 1997)
Stuck or slowed fermentations are costly in time and money to winemakers. There are many variables that can interrupt fermentation. One of the lesser known factors is the effect of fluoride on grape juice fermentations. Winemakers in California have had problems with slow or stuck fermentations with grapes that have been treated with the insecticide Cryolite, which contains fluoride. A selection of 6 yeasts, 3 commercial strains and 3 natural strains, commonly associated with winemaking were used in this study. Preliminary experiments investigated a wide range of fluoride challenge with different pH and cell densities on solid and liquid media. The effectiveness of fluoride was compared between sodium fluoride and Cryolite, as the fluoride source. The effect of fluoride was more potent with sodium fluoride, as the fluoride source. The minimum inhibitory concentration of fluoride for the yeast strains was recorded. The most sensitive commercial yeast was Saccharomyces cerevisiae RS1, the most resistant commercial yeast was Saccharomyces bayanus RS2. The most sensitive yeast overall was Hansenula saturnus AWRI-354. The next stage examined the effect of fluoride on the selected yeast in small scale grape juice fermentations. Within this investigation the effect of different media sources and heat treatments was included. Fluoride concentrations reflected levels of fluoride found in grape musts and wines. During this study we found that the effect of fluoride on yeasts is increased with lower pH and lower cell densities. The effect of fluoride on yeast growth and fermentation was also strain dependent.
Keywords: Microbiology; Wine and wine making; Yeast; Saccharomyces; Fermentation; Fluorides -- Physiological effect